Prevalence of Head Injury and Associated Disability in Prison Populations: A Systematic Review. Issue 4 (July 2018) - Moynan, Claire R.; McMillan, Tom M.
Abstract : Objective: This review systematically assesses literature on the prevalence of head injury (HI) and associated disability in adults in prison. Methods: Searches were carried out using electronic databases (PsycINFO, Cochrane Databases, MEDLINE, EMBASE, Web of Science). Reference lists of 2 meta-analyses were checked for relevant articles. Methods were rated for risk of bias. Results: The 10 studies included report a range in prevalence of HI in prisoners from 25% to 86%. Risk of bias was high overall, probably because a range of HI definitions was used, assessments were often not validated, and samples were not or not evidenced to be representative of the prison population. There was an absence of appropriate population controls from which to compare relative risk of HI in different countries. No study reported the prevalence of disability associated with HI. Conclusion: The wide range in prevalence estimates of HI in prisoners is associated with high risk of bias from study design and methods. Persisting disability associated with HI was not reported and as a result the service need for prisoners with HI is unclear. Future studies should indicate that samples are representative of prison populations, use validated tools and internationally accepted definitions of HI, and link prevalence to persisting disability.